Voltage drops studies for the operation of the microprocessor and microcircuits (Czech Journal of Multidisciplinary Innovations, 2022)
The article explores the possibility of using flexible circuits in rectifier systems. An optimal topology of the power converter is proposed, fully using the functionality of the microcircuits. The proposed solution generates a relatively smooth DC output with less high frequency harmonic content, avoiding the high frequency harmonic problems found in rectifiers and will play a significant role in improving profitability and reliability in low to medium range power rectifier systems.